LEARNING MODEL OF POLITE LANGUAGE BY CD INTERACTIVE LEARNING AT KINDERGARTEN THROUGHOUT WEST SUMATERA - Dr. Nenny Mahyuddin, M.Pd; Yeni Rozi Mela; Rismareni Pransiska (Universitas Muhammadiyah Ponorogo, 2019)
Any phenomenon at research field in which there is any trend that the children had not spoken a less polite language when they were in Kindergarten, for example, there were some words or sentences mocking friends, insulting, swearing using local languages during in the classroom, polite language in learning. This Interactive Multimedia is aimed for Kindergarten throughout West Sumatera. The used research type is so-called Research and Development (R D). This developmental research used a model of Interactive Multimedia (IMM) development or those had been developed by Rob Philips (1997). This model consists of five steps those are analysis, design, development, evaluation, and implementation. It had resulted in the researcher to know more in terms of efforts in order that those children will change those with more polite language such as words of sorry, excuse me, thank, please help me and others according to situation and condition faced by them. Any solution for solving the problem above is by using interactive multimedia.